Impact of adjusted kidney volume measured in the bench surgery on one-year renal function in kidney transplantation - Ordones, Flávio Vasconcelos [UNESP]; Pajolli, Pedro Ivo Rocchetti [UNESP]; da Silva, Rodrigo Guerra [UNESP]; Yamamoto, Hamilto Akihissa [UNESP]; Filho, Fernando Fereira Gomes [UNESP]; Kawano, Paulo Roberto [UNESP]; Amaro, João Luiz [UNESP]; de Andrade, Luis Gustavo Modelli [UNESP] (Public Library of Science (PLoS), 2019)
Background Kidney transplantation is the treatment of choice in patient with end stage chronic kidney disease, offering the best long term survival and greater Quality of Life in this group of patients. Graft volume was correlated with improved renal function in living donor transplantations. The primary aim of this study was to correlate renal volume adjusted to body surface area with renal function one year (estimated glomerular filtration rate; eGFR) after kidney transplantation. Methods This single-center, prospective cohort study included 256 patients who underwent kidney transplantation from January 2011 through December 2015 at Hospital das Clínicas de Botucatu–UNESP. We evaluated three kidney measurements during the bench surgery; the final graft volume was calculated using the ellipsoid formula and adjusted to body surface area. Results In the living donors there was positive correlation between adjusted graft volume and eGFR (r = 0.311, p = 0.008). Multivariate analysis revealed that low rejection rate and increased adjusted graft volume were independent factors correlated with eGFR. In deceased donors, there was no correlation between adjusted kidney volume and eGFR (r = 0.08, p = 0.279) in univariate analysis, but a multivariate analysis indicated that lower kidney donor profile index (KDPI), absence of rejection and high adjusted kidney volume were independent factors for better eGFR. Conclusion Adjusted kidney volume was positively correlated with a satisfactory eGFR at one year after living donor and deceased donor transplantations.